2016
DOI: 10.1111/bcp.12815
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of human fetal pharmacokinetics using ex vivo human placenta perfusion studies and physiologically based models

Abstract: AIMSPregnant women can be exposed to numerous drugs during the gestational period. For obvious ethical reasons, in vivo studies of fetal exposure to drugs are limited. Information about the transplacental transfer of drugs prior to their administration to pregnant women would be highly useful. In the present study, a novel approach was developed quantitatively predict or to predict the fetal exposure to drugs administered to the mother quantitatively. METHODSTransplacental parameters estimated from ex vivo hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 47 publications
4
55
0
Order By: Relevance
“…Various models have previously been presented that allow the prediction of concentrations in the fetal blood or tissues . The 2 most promising approaches for predicting the transfer of a compound across the placenta were those presented by De Sousa Mendes et al and by Zhang et al . The approach suggested by Mendes et al relies on experimental data obtained from the ex vivo cotyledon perfusion experiment.…”
Section: Models For Placental Drug Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…Various models have previously been presented that allow the prediction of concentrations in the fetal blood or tissues . The 2 most promising approaches for predicting the transfer of a compound across the placenta were those presented by De Sousa Mendes et al and by Zhang et al . The approach suggested by Mendes et al relies on experimental data obtained from the ex vivo cotyledon perfusion experiment.…”
Section: Models For Placental Drug Transfermentioning
confidence: 99%
“…Thereafter, these parameters were integrated in a whole‐body PBPK model. It was shown that through this approach, the pharmacokinetics of emtricitabine, tenofovir, and nevirapine observed at delivery could adequately be predicted by the PBPK model . One shortcoming of this approach is that it cannot be readily extrapolated to other compounds for which no data from the ex vivo cotyledon perfusion experiment are available.…”
Section: Models For Placental Drug Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, originating from the Simcyp pregnancy model, more mechanistic PBPK models were recently developed in R, 46,47 MatLab, 40,48 and Berkeley Madonna. 49 Instead of a lumped fetoplacental unit, the models developed in R and MatLab incorporate four separate compartments representing the amniotic fluid, fetal body, fetal blood, and the placenta.…”
Section: Model Structurementioning
confidence: 99%
“…Another approach has been proposed by De Sousa Mendes et al, who estimated placental transfer rates for tenofovir, emtricitabine, and nevirapine from ex vivo placenta perfusion experiments. 46,47 The estimated transfer rates were subsequently implemented in a PBPK model framework and fetal exposure was adequately predicted. Schalkwijk et al employed a very similar approach for predicting fetal darunavir exposure.…”
Section: Placental Drug Transfer and Fetal Pharmacokineticsmentioning
confidence: 99%